2006
DOI: 10.3727/152599506779364660
|View full text |Cite
|
Sign up to set email alerts
|

Motivations of Young People for Visiting Wine Festivals

Abstract: This article investigates the motivations of young visitors (35 years old and under) at two wine festivals in Texas and Indiana. Fourteen motivational items were identified in which tasting wine, being entertained, and being with friends were perceived to be important motives for young visitors. In addition, differences were compared between the young and older visitors. Young people were found to attach more importance to enjoying entertainment, finding thrills and excitement, and being with friends. Interes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 15 publications
1
36
0
Order By: Relevance
“…As well as focusing on the cross-cultural validation of motivation wine (Hall, 1996), wine knowledge (Charters & Ali-Knight, 2002;Mitchell & Hall, 2001a, 2001bJ. J. Yuan et al, 2005a), generations (Dodd, Yuan, Adams, & Kolyesnikova, 2006), country of origin (Alonso, Fraser, & Cohen, 2007), repeat visitors versus first timers (Bruwer & Lesschaeve, 2012), and festival information sources (Shanka & Taylor, 2004), rather than motivations. Because this study does not contextualize the Dalian festival directly within tourism studies and the notion of a discrete Chinese wine festival tourist seeking a total tourism experience, we hope to create new knowledge gap about festival motivations.…”
Section: Wine Tourism and Wine Festivalsmentioning
confidence: 99%
“…As well as focusing on the cross-cultural validation of motivation wine (Hall, 1996), wine knowledge (Charters & Ali-Knight, 2002;Mitchell & Hall, 2001a, 2001bJ. J. Yuan et al, 2005a), generations (Dodd, Yuan, Adams, & Kolyesnikova, 2006), country of origin (Alonso, Fraser, & Cohen, 2007), repeat visitors versus first timers (Bruwer & Lesschaeve, 2012), and festival information sources (Shanka & Taylor, 2004), rather than motivations. Because this study does not contextualize the Dalian festival directly within tourism studies and the notion of a discrete Chinese wine festival tourist seeking a total tourism experience, we hope to create new knowledge gap about festival motivations.…”
Section: Wine Tourism and Wine Festivalsmentioning
confidence: 99%
“…The push and pull model (Crompton, 1979;Dann, 1977Dann, , 1981 is well accepted in tourist motivation studies (Funk, Alexandris, & Ping, 2009;Mak, Wong, & Chang, 2009;Uysal, Li, & Sirkaya-Turk, 2008) and has been applied in various cultural settings (Hanqin & Lam, 1999;Schofield 4 & Thompson, 2007;and Yuan & McDonald, 1990). It has also been applied in several event motivation studies within different cultural settings, for example, Zyl and Botha's (2004) study in South Africa, several studies in the USA (Bowen & Daniels, 2005;Dodd et al, 2006), and Chang's (2005) study in Taiwan. This suggests that this model is considered to be a useful tool to generally analyse and understand attendees' motivations to attend events.…”
Section: Festival-goer Motivationmentioning
confidence: 99%
“…The push and pull model (Crompton, 1979) and escape-seek motivation theory (Iso-Ahola, 1982) have both provided conceptual frameworks and have been used in many later studies related to festivals, for example Chang (2005), Dodd, Yuan, Adams, & Kolyesnikova (2006), and Mohr, Backman, K.F., Gahan, & Backman, S.J. (1993).…”
Section: Introductionmentioning
confidence: 99%
“…The literature on event motivation describes two types of socialization as motives for visiting the have indicated that the social aspect of the event experience is an important motive for visiting events (e.g., Dodd, Yuan, Adams, & Kolysnikova, 2006;Nicholson & Pearce, 2001). People go to events to socialize with friends and family (e.g., Chang & Yuan, 2011), to meet new people (e.g., Crompton & McKay, 1997), or to experience the positive atmosphere that is created when people gather together to have fun (e.g., Gelder & Robinson, 2009).…”
Section: The Social Aspect Of the Event Experiencementioning
confidence: 99%